Chemical resistance of core-shell particles (PS/PMMA) polymerized by seeded suspension - Ribeiro,Luiz Fernando Belchior (2017)
Abstract Core-shell particles were produced on seeded suspension polymerization by using polystyrene (PS) as polymer core, or seed, and methyl methacrylate (MMA) as the shell forming monomer. Two synthesis routes were evaluated by varying the PS seed conversion before MMA addition. The main purpose of this work was to investigate the influence of synthesis routes on the morphology and chemical resistance of the resulting particles. 1H NMR spectroscopy showed that the use of PS seeds with lower conversion led to the formation of higher amount of poly(styrene-co-MMA). The copolymer acted as a compatibilizer, decreasing the interfacial energy between both homopolymers. As a consequence, a larger amount of reduced PMMA cluster were formed, as was revealed by TEM measurements. Samples in this system showed enhanced resistance to cyclohexane attack compared with pure PS, with a PS extraction of only 37% after 54 hours test.